2000
DOI: 10.1046/j.1365-2141.2000.01796.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and laboratory evidence for a trilineage haematopoietic defect in patients with refractory Diamond–Blackfan anaemia

Abstract: Summary. Diamond±Blackfan anaemia (DBA) is a constitutional pure red cell aplasia presenting in early childhood. In some patients, neutropenia and/or thrombocytopenia have also been observed during the course of the disease. We have followed 28 patients with steroid-refractory DBA for up to 13 years with serial peripheral blood counts and bone marrow (BM) aspirates and biopsies. In 21/28 (75%) patients, moderate to severe generalized BM hypoplasia developed, with overall cellularities ranging from 0% to 30%. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
64
0
4

Year Published

2001
2001
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(74 citation statements)
references
References 40 publications
6
64
0
4
Order By: Relevance
“…Measurement of eADA is considered a reasonably reliable indicator of DBA and a minor diagnostic criterion in DBA (Orfali et al, 2004;Vlachos et al, 2008), whereas the incidence of eADA elevation in severe aplastic anaemia (SAA) has not been studied to date. In addition to the unusual presentation of non-classical DBA in a young adult, this case is distinguished by progressive pancytopenia (not currently considered a diagnostic criteria for DBA; Diamond et al, 1976) that, unlike reported cases of trilineage haematopoietic defects in DBA, preceded treatment, (Giri et al, 2000). We suggest that DBA should therefore be considered in any patient with hypoplastic pancytopenia and macrocytosis, especially in the absence of the severe bone marrow hypocellularity that is characteristic of severe AA, regardless of age.…”
mentioning
confidence: 99%
“…Measurement of eADA is considered a reasonably reliable indicator of DBA and a minor diagnostic criterion in DBA (Orfali et al, 2004;Vlachos et al, 2008), whereas the incidence of eADA elevation in severe aplastic anaemia (SAA) has not been studied to date. In addition to the unusual presentation of non-classical DBA in a young adult, this case is distinguished by progressive pancytopenia (not currently considered a diagnostic criteria for DBA; Diamond et al, 1976) that, unlike reported cases of trilineage haematopoietic defects in DBA, preceded treatment, (Giri et al, 2000). We suggest that DBA should therefore be considered in any patient with hypoplastic pancytopenia and macrocytosis, especially in the absence of the severe bone marrow hypocellularity that is characteristic of severe AA, regardless of age.…”
mentioning
confidence: 99%
“…20 Although present at normal frequencies, the proliferation and differentiation of immature hematopoietic progenitors in DBA have shown to be impaired in vitro. 2,18,20,21 Generation of animal models for RPS19-deficient DBA is pivotal to understand the disease mechanisms and to evaluate novel therapies. Matsson et al attempted to create a mouse model with a targeted disruption of Rps19.…”
Section: Introductionmentioning
confidence: 99%
“…Néanmoins, cette question reste discutée : d'autres travaux ont fait le constat d'une réduction du nombre de progéniteurs précoces BFU-e, ce qui suggère un défaut plus en amont dans la hiérarchie de l'hématopoïèse [9,10]. En accord avec cette idée, il a été montré que la différenciation d'autres lignages hématopoïétiques pouvait être affectée chez certains patients [11,12].…”
Section: L'anémie De Diamond-blackfanunclassified
“…La cartographie pangénomique des SNP (single nucleotide polymorphisms) réalisée dans 215 familles a révélé d'autres locus en lien avec l'ADB : une région de 18 Mb sur le chromosome 8 (8p23. [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] et des régions plus petites sur les chromosomes 6 et 10. Concernant le chromosome 10, le séquençage du gène codant la protéine ribosomique RPS24 a mis en évidence chez trois patients deux mutations non-sens et une délétion de la région codante, absentes lors de l'analyse de 200 génomes contrôles [15].…”
Section: L'adb Est Associée à Des Mutations Dans Des Protéines Ribosounclassified